Validation of the Transition Readiness and Appropriateness Measure (TRAM) for the Managing the Link and Strengthening Transition from Child to Adult Mental Healthcare in Europe (MILESTONE) study. Issue 6 (23rd June 2020) - Santosh, Paramala; Singh, Jatinder; Adams, Laura; Mastroianni, Mathilde; Heaney, Natalie; Lievesley, Kate; Sagar-Ouriaghli, Ilyas; Allibrio, Giovanni; Appleton, Rebecca; Davidović, Nikolina; de Girolamo, Giovanni; Dieleman, Gwen; et al.
Abstract : Objective: Young people moving from child and adolescent mental health services (CAMHS) to adult mental health services (AMHS) are faced with significant challenges. To improve this state of affairs, there needs to be a recognition of the problem and initiatives and an urgent requirement for appropriate tools for measuring readiness and outcomes at the transfer boundary (16–18 years of age in Europe). The objective of this study was to develop and validate the Transition Readiness and Appropriateness Measure (TRAM) for assessing a young person's readiness for transition, and their outcomes at the transfer boundary. Design: MILESTONE prospective study. Setting: Eight European Union (EU) countries participating in the EU-funded MILESTONE study. Participants: The first phase (MILESTONE validation study) involved 100 adolescents (pre-transition), young adults (post-transition), parents/carers and both CAMHS and AMHS clinicians. The second phase (MILESTONE cohort study and nested cluster randomised trial) involved over 1000 young people. Results: The development of the TRAM began with a literature review on transitioning and a review of important items regarding transition by a panel of 34 mental health experts. A list of 64 items of potential importance were identified, which together comprised the TRAM. The psychometric properties of the different versions of the TRAM were evaluated and showed that the TRAM had good reliability for all versions and low-to-moderate correlations when compared with other established instruments and a well-defined factor structure. The main results of the cohort study with the nested cluster randomised trial are not reported. Conclusion: The TRAM is a reliable instrument for assessing transition readiness and appropriateness. It highlighted the barriers to a successful transition and informed clinicians, identifying areas which clinicians on both sides of the transfer boundary can work on to ease the transition for the young person. Trial registration number: ISRCTN83240263 (Registered 23 July 2015), NCT03013595 (Registered 6 January 2017); Pre-results.